The impact of hydromorphone combined with ropivacaine in serratus anterior plane block on postoperative pain in patients undergoing video-assisted thoracoscopic pulmonary lobectomy: a randomized, double-blind clinical trial - Xuefeng Chen; Weifeng Zhang; Lin Wang; Weibing Wang; Yuhong Li (BMC Anesthesiology)
Abstract Background This study aimed to assess the effects of hydromorphone as an adjuvant to ropivacaine serratus anterior plane block (SAPB) on postoperative analgesia and inflammatory responses in patients undergoing video-assisted thoracoscopic surgery (VATS). Methods This was a prospective, randomized, double-blind clinical trial. A total of 120 lung cancer patients, aged 20–75 years, with an American Society of Anesthesiologists classification of I or II and a body mass index of 18–28 kg/m², were randomly assigned to three groups: ropivacaine combined with hydromorphone SAPB (HR group), ropivacaine SAPB (R group), and control (C group). Ultrasound-guided deep SAPB was used to inject medications. The main observed indicators were postoperative visual analog scale (VAS) pain scores, serum inflammatory markers (C-reactive protein (CRP), IL-6, TNF-α), intraoperative medication dosage, postoperative complication rates, and analgesic effects. Results Postoperative VAS pain scores were significantly reduced in the HR and R groups compared to the C group, especially at 6 h postoperatively. The median VAS score in the HR group was 2.00 (inter-quartile ratio (IQR): 2.00, 2.00), which was significantly lower than that of the C group’s score of 3.00 (IQR: 3.00, 3.00; P < 0.001). The CRP levels at 24 and 48 h postoperatively in the HR group were 23.80 mg/L and 21.65 mg/L, respectively, significantly lower than the C group’s levels of 56.65 mg/L and 82.75 mg/L, P < 0.001. The levels of IL-6 and TNF-α were also significantly lower in the HR group than in the C group. Intraoperative propofol and remifentanil dosages in the HR group were reduced to 5.22 mg/kg/h and 7.59 µg/kg/h, respectively, lower than the C group’s dosages of 5.93 mg/kg/h and 5.74 µg/kg/h, P < 0.001. The incidence of postoperative nausea and vomiting in the HR group was 12.5%, which was lower than that in Group C (35.7%, P = 0.032). Conclusion Ropivacaine adjuvant with hydromorphone in SAPB reducing postoperative pain and inflammatory in patients undergoing VATS, which contributed to rapid recovery. However, future studies should explore the long-term benefits and concenntration of hydromorphone of SAPB before it taken into clinical use. Trial registration Chinese Clinical Trial Register on August 19, 2021, NCT number ChiCTR2100053893.